2022
DOI: 10.1155/2022/1189034
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Anticancer Mechanisms and Synergistic Combinations of Phytochemicals with Cancer Chemotherapeutics: Potential Benefits and Risks

Abstract: Cancer therapies are associated with various challenges including the emergence of multidrug resistant tumors, toxicological issues, severe side effects, and economic burden. To counteract these effects, natural products as substitutes and adjuvant therapies have received considerable attention owing to their safety, efficacy, and economic aspects. Various preclinical and clinical studies revealed that natural products and their combinations with chemotherapeutics mediate their anticancer effects via modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Flavonoids are a well-defined class of polyphenolic synthetic or natural compounds [ 11 , 12 ], usually found in wine, vegetables, fruits, cereals and tea and have considerable pharmacological activities such as antioxidant [ 13 , 14 ], anticancer [ 15 , 16 , 17 , 18 ], anti-Alzheimer [ 19 , 20 ], anti-inflammatory [ 21 , 22 , 23 ] and anxiolytic [ 24 ]. Flavonoids and their derivatives have been extensively studied for their beneficial analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are a well-defined class of polyphenolic synthetic or natural compounds [ 11 , 12 ], usually found in wine, vegetables, fruits, cereals and tea and have considerable pharmacological activities such as antioxidant [ 13 , 14 ], anticancer [ 15 , 16 , 17 , 18 ], anti-Alzheimer [ 19 , 20 ], anti-inflammatory [ 21 , 22 , 23 ] and anxiolytic [ 24 ]. Flavonoids and their derivatives have been extensively studied for their beneficial analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the natural products have been considered rich in phytochemicals such as glycosides, renins, tannins, flavonoids, polyphenol, alkaloids, and terpenoids [18][19][20]. These active ingredients present in the natural products like plants possess antioxidant, anti-inflammatory, antifungal, antimicrobial, antimycotic, and anticancer properties [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Tese problems have led to a renewed interest in plant-based medicines due to their better tolerability and lower number of side efects. Plants have been used as medicine to maintain human health for ages and are also major natural sources of medicinal compounds in current pharmacopoeias [28,29]. Te current study demonstrated the protective efect of the hydroalcoholic fg extract of Ficus benjamina L. (FBE) on picrotoxin and maximal electroshock-induced convulsions in mice.…”
Section: Discussionmentioning
confidence: 61%